PERSEPSI MAHASISWA AKUNTANSI DAN MANAJEMEN TERHADAP PERILAKU MENABUNG PERIODE COVID-19 - Hurian Kamela; Noorlailie Soewarno (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
Saving behavior needs to be done by the community, especially students. It aims to measure how much accounting and management students assess their saving behavior during the COVID-19 period. The number of respondents for this study is 73 people from November-December 2021. The samples taken are accounting and management students since they must know finance basics. The research method is multiple linear regression with STATA application. The dependent variable is saving behavior. The independent variables are actions in saving, knowledge about savings, and an assessment of savings. The study results prove that there is no effect of saving action on saving behavior. It proves that accounting and management students are not too focused on their finances to save, even though during the COVID-19 pandemic period, it is necessary to have savings with a precautionary motive. This contribution explains the need for students to be more concerned about finances, especially saving behavior.